2022
DOI: 10.37349/emed.2022.00077
|View full text |Cite
|
Sign up to set email alerts
|

Placental CD4+ T cells from preeclamptic patients cause autoantibodies to the angiotensin II type I receptor and hypertension in a pregnant rat model of preeclampsia

Abstract: Aim: Preeclampsia (PE) is a hypertensive disorder of pregnancy associated with activated CD4+ T cells and autoantibodies to angiotensin II type 1 receptor (AT1-AA). We have previously shown that CD4+ T cells isolated from women with PE cause hypertension, increased tumor necrosis factor alpha (TNF-α), endothelin-1, and soluble fms-like tyrosine kinase-1 (sFlt-1) when injected into pregnant nude-athymic rats compared to CD4+ T cells from normal pregnant (NP) women. However, the role of PE CD4+ T cells to cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…We have also shown that T cells isolated from patients with PE can cause PE symptoms in pregnant nude-athymic rats (75). More recently, we showed that incubation with anti-CD40L before adoptive transfer also improved PE symptoms in the nude-athymic model, further indicating that T cells costimulating B cells is critical to the pathophysiology of PE (64).…”
Section: T Cells In Normal Pregnancy and Preeclampsiamentioning
confidence: 87%
See 1 more Smart Citation
“…We have also shown that T cells isolated from patients with PE can cause PE symptoms in pregnant nude-athymic rats (75). More recently, we showed that incubation with anti-CD40L before adoptive transfer also improved PE symptoms in the nude-athymic model, further indicating that T cells costimulating B cells is critical to the pathophysiology of PE (64).…”
Section: T Cells In Normal Pregnancy and Preeclampsiamentioning
confidence: 87%
“…Studies also demonstrate that inflammatory cytokines, such as TNF- α , IL-6, and IL-17, play crucial roles in immune activation by increasing the production of vasoactive molecules, such as AT1-AA, ET-1, and sFlt-1 (61 63). Importantly we recently showed that adoptive transfer of CD4+ T cells from placentas of patients with PE causes hypertension; intrauterine growth retardation; and increased AT1-AA, sFlt-1, ET-1, and the cytokines TNF- α and IL-17, demonstrating the importance of T cells in causing many characteristics of PE (64).…”
Section: T Cells In Normal Pregnancy and Preeclampsiamentioning
confidence: 99%
“…We have demonstrated the importance of T cell‐B cell communication as an important step in the pathophysiology of hypertension and AT1‐AA production in the RUPP rat model of placental ischemia 20,21 . T cell‐B cell communication is a pivotal step in B cell activation and formation of immune memory, 22 allowing for long‐term production of antibodies after antigen exposure.…”
Section: Introductionmentioning
confidence: 94%
“…We have demonstrated the importance of T cell-B cell communication as an important step in the pathophysiology of hypertension and AT1-AA production in the RUPP rat model of placental ischemia. 20,21 T cell-B cell communication is a pivotal step in B cell activation and formation of immune memory, 22 allowing for long-term production of antibodies after antigen exposure. We have shown that B cell depletion with Rituximab attenuates the hypertension associated with placental ischemia in the RUPP preclinical model of placental ischemia; therefore, implicating a role for B cells in PE pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Our lab has shown that Th cells stimulated by placental ischemia from rats or humans induce hypertension, mitochondrial dysfunction, sflt-1, AT1-AA, and other features of PE in pregnant rats (Deer et al, 2021;Reeve et al, 2022). However, blockade of communication between Th cells and B cells prevents the features of PE induced by Th cell adoptive transfer (Cornelius et al, 2015).…”
Section: T Helper Cells and B Cells In Preeclampsiamentioning
confidence: 99%